Decentralized storage technology of network information security level secret key of distribution automation terminal - Jin Yi; Weijie Huang; Lianghao Huang; Guozheng Huang; Guangyong Zheng; Yongle Li (Discover Applied Sciences)
Abstract To improve the management efficiency of network information in distribution automation terminals, a study was conducted on the decentralized storage technology of network information security level keys for distribution automation terminals. This technology utilizes a linear geometric hierarchical management scheme, manages keys through a key derivation tree structure, and encompasses the construction of key derivation trees, secure storage of root keys, and key exchange protocols to achieve effective distribution of keys in the network. Experimental results have shown that this technology can flexibly manage the keys of distribution automation terminals based on information security levels, improving the management efficiency of network information.